Konsep ‘Imago Dei’ Emmanuel Levinas - Yohanes E. Vinsen (FOCUS, 2020)
One’s Identity is a vital component of a human life. Identity is important, es- pecially considering when oneself is sometimes subjected to the judgment of others. Emmanuel Levinas initiated the concept of the ‘Imago Dei’ to reduce negative judgment whilst simultaneously elevating individual uniqueness based upon our natures as im- ages of God. The idea of ‘imago Dei’ manifests in one’s face. Our visage then becomes a non-verbal media of communication akin to a conversation expressing one’s identity whereas a dialectical exchange would otherwise prove cumbersome. An understanding of the ‘imago Dei’ brings people towards the awareness of their statuses as God’s cre- ations, creations most associated with Him to the extent he deigned designated them His very images.